Review of AI Image Enhancement Techniques for In-Vehicle Vision Systems Under Adverse Weather Conditions - Tiande Mo; Siqian Zheng; Wai-Yat Chan; Renhua Yang (World Electric Vehicle Journal)
Nowadays, rapid advancements in computer vision, image processing, and artificial intelligence (AI) have significantly benefited autonomous vehicles. Visual perception is crucial for enhancing the functionality and safety of self-driving technology. However, adverse weather and illumination conditions can impair visual capabilities, affecting environmental awareness, decision-making, and safe navigation. This work provides a comprehensive review of AI image enhancement methods and benchmark datasets, including deblurring, deraining, dehazing, and low-light enhancement, along with the integration of multiple image enhancement techniques in computer vision tasks. Specifically, this review focuses on advancements for real-world applications and summarizes performance metrics for real-time operation in automotive vision systems. Furthermore, the paper highlights efforts and challenges in real-world testing to ensure the effectiveness and reliability of these solutions in practical applications, which is essential for enabling autonomous vehicles to operate safely and efficiently under various challenging conditions, thereby contributing to the future of intelligent transportation systems.